A novel approach to reveal Gender in Food Systems through Big Data - CGIAR Platform for Big Data in Agriculture (2019)
The partners combined a phone-based survey with analysis of many billions of data points generated by the operation of mobile phone networks to predict sex and decision power among female farmers in Uganda.